Towards formal evaluation of collaborative work - R. Baeza-Yates; J.A. Pino (Information Research: An International Electronic Journal)
Introduction. Computer Supported Cooperative Work (CSCW) projects are difficult to evaluate when implemented at most organizations. There are many variables and some of these are qualitative and hard to assess. However, there are other variables that could be measured and, thus, for a specific CSCW system, management could have a performance estimate. Method. A groupware application is modelled, focusing on the work done and time spent on the collaboration. Analysis. The following variables and their relations are studied: quality of the outcomes, number of people involved and time spent on the overall task, and total work done. Results. An application - collaborative retrieval - is formalized to illustrate the model. For this application, a specific heuristic is proposed to the case when many people search for the same information, thereby increasing the recall and precision of the answer. The evaluation methodology is applied to this case, showing some experimental results. Conclusion. We present an initial attempt to formally evaluate performance measures related to CSCW applications.